Exclusionary secularism: the Front national and the reinvention of laïcité. (3rd July 2017) - Almeida, Dimitri
Abstract: After two decades of privileged relations with Catholic traditionalism, the Front national (FN) now presents itself as the staunchest defender of laïcité . This article aims to examine this alleged secular turn by analysing its relation with Marine Le Pen's strategy of normalisation. It argues that laïcité in today's bleu marine FN must be understood both as a new frame to legitimise old preferences and as a strategy to reach heterogeneous constituencies. Furthermore, the article places the FN's understanding of laïcité into the larger context of the diffusion of exclusionary readings of French secularism since 1989.